Evaluation of fresh wood weight using dimensional variables in two species of mezquite Prosopis articulata S. Watson and P. palmeri S. Watson, in Baja California Sur, Mexico - León de la Luz, José Luis; Domínguez Cadena, Raymundo; Díaz Castro, Sara Cecilia (Instituto de Ecología, A.C., 2005)
Using regression models, this research determines the fresh woody biomass for two species of mezquite (Prosopis articulata and P. palmeri) currently used as raw material to make charcoal in Sierra de la Giganta, Baja California Sur, Mexico. This practice began many decades ago, but only since 1990 production data based on issued permissions are available. The independent variables better correlated with the fresh wood weight in a destructive sample were the basal perimeter of the stems for P. articulata (R2 = 0.98, F = 394.12), and the canopy coverage for P. palmeri (R2 = 0.94, F = 63.26). The empirical models employed in these calculations were logarithmic and exponential, respectively.  In order to apply these formulas, the appropriate independent variable for each species was used to estimate fresh wood weight in 11 plots of one hectare.  1,283 individuals of P. palmeri and 755 individuals of P. articulata were non-destructively sampled. By employing these calculations, we determined that the biomass useful for charcoal production was 37,040 kg/ha for P. articulata and 2,045 kg/ha for P. palmeri.  If each species is harvested exclusively and in accordance with the quantity of wood officially authorized to be gathered during the decade of 1990, these values represent an annual harvest for all the individuals with the adequate size for this purpose (trunk basal diameter > 10 cm) of 179 hectares of P. articulata along riparian areas or 3,928 hectares of P. palmeri on mesas and slopes.